1982
DOI: 10.1002/pen.760221410
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Oxidation and photo‐stabilization of blends of low‐density polyethylene and styrene‐butadiene‐styrene copolymers

Abstract: The photo‐oxidation of blends of low‐density polyethylene and styrene‐butadiene‐styrene block copolymers has, been shown to result mainly from the degradation of the pollybutadiene part of the material. The solution infra‐red and fluorescence spectra, and mechanical properties have been studied as a function of the irradiation time. Evidence of some interaction between the components of the blend could be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Several papers suggest that the interaction between polymers which form the blend 1131,1134,1141,1142,[1146][1147][1148] leads to the formation of block copolymers. This is caused by radicals which are formed during the photodegradation.…”
Section: Polymer Blendsmentioning
confidence: 99%
“…Several papers suggest that the interaction between polymers which form the blend 1131,1134,1141,1142,[1146][1147][1148] leads to the formation of block copolymers. This is caused by radicals which are formed during the photodegradation.…”
Section: Polymer Blendsmentioning
confidence: 99%
“…Badr et al [11] have also observed different behavior of the fluorescence of LDPE either in the peak position or height upon varying the type of irradiation in addition to the dose of absorbed radiation. David et al [12] have studied the interaction between the components of blends in the course of the photo-oxidation or of the degradation induced by ionizing radiation as a function of their degree of compatibility and of the methods of processing of the material. Konar and Ghosh [13] have used solid state fluorescence spectra to characterize the oxidation of LDPE by potassium permanganate.…”
Section: Introductionmentioning
confidence: 99%